A command layer for anisotropic plasmonic photo-thermal effects in liquid crystal. Issue 13 (8th December 2018) - Palermo, Giovanna; Guglielmelli, Alexa; Pezzi, Luigia; Cataldi, Ugo; De Sio, Luciano; Caputo, Roberto; De Luca, Antonio; Bürgi, Thomas; Tabiryan, Nelson; Umeton, Cesare
ABSTRACT: Photo-anisotropic properties of a particular command layer for Liquid Crystals (LCs), based on azo-benzene material, are exploited to control the photo-thermal response of a single layer of homogeneously and uniformly distributed Au nanoparticles, immobilised on a glass substrate. Experiments demonstrate that the intrinsic anisotropy of materials can influence the photo-thermal response of plasmonic systems. Indeed, the resonant absorption of radiation by plasmonic subunits is followed by a noticeable increase of their temperature. However, the thermal response observed in presence of a homogeneous and random array of AuNPs directly exposed to air or embedded in ice is typically isotropic; on the contrary, a homogenous, yet thin, coating made of a particular command layer for LCs, deposited on a large-area carpet of AuNPs, influences their thermal response in an anisotropic way. In particular, the temperature increase, induced by pumping with a laser source of resonant wavelength with the plasmonic AuNPs, strongly depends on the alignment direction of the command layer. This effect makes the command layer of particular interest for its capability to drive intriguing optically induced 'thermal-reorientational' effects in a liquid crystal film. Graphical Abstract: